Molecular subtypes of colorectal cancers determined by PCR‐based analysis. Issue 3 (3rd April 2017) - Sugai, Tamotsu; Eizuka, Makoto; Takahashi, Yayoi; Fukagawa, Tomoyuki; Habano, Wataru; Yamamoto, Eiichiro; Akasaka, Risaburo; Otuska, Kouki; Matsumoto, Takayuki; Suzuki, Hiromu
Abstract : Tumor tissue consists of a heterogeneous cell population. The allelic imbalance (AI) ratio, determined in isolated tumor glands, is a good index of tumor heterogeneity. However, associations of the patterns of AI and microsatellite instability (MSI) development, observed in most cases of colorectal cancer (CRC), with tumor progression have not been reported previously. In this study, we examined whether CRC genetic profiles stratified by a combination of the AI ratio and MSI facilitate categorization of CRC, and whether these genetic profiles are associated with specific molecular alterations in CRC. A crypt isolation method was used to isolate DNA from tumors and normal glands obtained from 147 sporadic CRCs. AI and MSI statuses were determined using PCR‐based microsatellite analysis and stratified based on AI ratio and MSI status. DNA methylation status (high methylation, intermediate methylation and low methylation status and mutations in KRAS, BRAF, and TP53 were examined. In addition, mucin markers were immunostained. Based on this analysis, four subgroups were categorized. Subgroup 1 was characterized by a high MSI status and BRAF mutation; subgroup 2 was closely associated with a high AI ratio, which accumulated during the early phases of colorectal carcinogenesis, and TP53 mutation; subgroup 3 was associated with a low AI ratio, seen during the later phases of colorectal carcinogenesis, and KRAS mutation; and subgroup 4 was defined as a minor subgroup. These results confirmed that classification of distinct molecular profiles provides important insights into colorectal carcinogenesis. Abstract : We examined whether genetic profiles stratified by a PCR‐based microsatellite method could facilitate categorization of CRCs and whether the genetic profile was associated with specific molecular alterations in CRCs. Our data confirmed that classification of distinct molecular profiles provided important insights into colorectal carcinogenesis, suggesting potential therapeutic implications of these molecular profiles.